Reaction of the half-sibling progeny obtained from the BRS Bravo rootstock to citrus tristeza virus - de Almeida dos Santos, Luana Laís; Pereira Costa, Danilo; Moreira Oliveira, Raquel; Araújo dos Santos, Samuel; Santos de Araujo, Sandriele; dos Santos Maciel, Edilane; dos Santos Soares Filho, Walter; de Jesus Barbosa, Cristiane (Pesquisa Agropecuaria Brasileira, 2026)
The objective of this work was to evaluate the reaction of citrus hybrids to natural infection by local isolates of the citrus tristeza virus (CTV; species: Closterovirus tristezae). Half-siblings obtained through open pollination were evaluated, and cultivar BRS Bravo, known for its tolerance to CTV, was used as the female parent. The experiment was conducted at the experimental field of Embrapa Mandioca e Fruticultura and involved 1,329 hybrids. Of these, 130 individuals were selected at 5–6 years of age, based on visual evaluations of vigor to favor plants with a vigorous vegetative growth through the mass selection method. The reaction to CTV was evaluated by the presence and severity of stem pitting symptoms. For this, ten branches per plant analyzed on a scale from 1 (absence) to 5 (entire surface covered by superficial or deep pits). CTV infection was determined by indirect ELISA using a polyclonal antiserum against CTV. Samples that tested negative in the serological assay were further analyzed by RT–PCR using primers F-CN119 (5’-AGATCTACCATGGACGACGAAACAAAG-3’) and R-CN120 (5’-GAATTCGCGGCCGCTCAACGTGTGTTAAATTTCC-3’). Data were subjected to the principal component analysis, which showed that 46.9% of the hybrids were classified as tolerant and 53.1% as resistant to CTV, highlighting their potential for the selection of new citrus rootstocks.